PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK MATERI SEGI EMPAT KELAS IV SD - Yulia Darniyanti; Suci Rahma Putri; Hesti Rahayu (STKIP Subang, 2023)
The purpose of this research is to make comic learning media for fourth grade quadrilateral material in order to add insight into learning media and can be used in schools so as to produce learning media that are valid, practical, and effective. It can also increase students' understanding of concepts and learning outcomes at SDN 189/II Sari Mulya. In the loading process, this comic learning media uses the help of an application called comic life 3. The development model used is the ADDIE model or analysis, development design, implementation and evaluation. Based on the results of the validation test from 3 validators, namely content, graphics and language validators, the average value was 86.54 with a very valid category. Practicality test results by practicing educators and students obtained an average value of 91.00 in the very practical category. The results of the effectiveness test in the form of a learning achievement test obtained from students obtained an average score of 98.46 in the very effective category.